Contextual Meaning on the Idiomatic Expressions in the Novel Before the Coffee Gets Cold - Syahwa Indah Kirana; La Sunra; Abdullah Abdullah (State University of Makassar, 2026)
The novel written by Toshikazu Kawaguchi with the title Before the Coffee Gets Cold uses a Japanese background, or rather Tokyo. The author explains that there is one located in a small alley in Tokyo. The age of the cafe is long enough or even you could say it's quite old. This research aims to identify idiomatic expressions in the novel. Idiomatic expression is a type of informal language which has a different meaning from the meaning of the words in that expression. “Hold Your Tongue” this idiom does not actually mean that you have to put your finger in your mouth and hold your tongue, it means that you should not talk. The theory used in this research is the theory from McCarthy and O'Dell (2010), where McCharty and O'Dell proposed 7 types of idioms, namely: similes, binomials, trinomials, euphemisms, proverbs, cliches, and fixed statements. This research uses a qualitative data analysis method based on Miles, Huberman and Saldana (2014). Data was taken from Toshikazu Kawaguchi's novel